2016
DOI: 10.1039/c6ta05043c
|View full text |Cite
|
Sign up to set email alerts
|

High performance bifunctional electrocatalytic activity of a reduced graphene oxide–molybdenum oxide hybrid catalyst

Abstract: The rGO–MoO3nanosphere hybrid synthesized exceeds the performance of high quality commercial Pt/C in terms of electrocatalytic activity, stability, durability and CO tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…For detailed comparison with all references, see Table S4. † Notably, we observed superior performance also when comparing the activity of 3 with that of literature-reported ORR catalysts based on crystalline MoO 3 , 49,50 highlighting that the high dispersion of [Mo-oxo] n clusters on high surface-area carbon leads to improved ORR electrocatalysts. Moreover, composite 3 showed better or similar electrocatalytic ORR activities compared with reported metal oxide clusters or even noble metal (e.g.…”
Section: Orr Activity Of Composites 1 2 Andsupporting
confidence: 50%
“…For detailed comparison with all references, see Table S4. † Notably, we observed superior performance also when comparing the activity of 3 with that of literature-reported ORR catalysts based on crystalline MoO 3 , 49,50 highlighting that the high dispersion of [Mo-oxo] n clusters on high surface-area carbon leads to improved ORR electrocatalysts. Moreover, composite 3 showed better or similar electrocatalytic ORR activities compared with reported metal oxide clusters or even noble metal (e.g.…”
Section: Orr Activity Of Composites 1 2 Andsupporting
confidence: 50%
“…In addition, most of these Magnéli phases can be grown into large single crystals to investigate the effects of orientation. Furthermore, Chandrasekaran et al recently reported that molybdenum oxide‐based compounds with different structures and properties can demonstrate excellent OER and ORR activities; attracting considerable interest in the field of materials research. There are few studies into the use of MoO 3 as catalysts or catalyst supports.…”
Section: Advancements Of Tm‐based Electrocatalystsmentioning
confidence: 99%
“…83 In particularly, MoO 3 , and to a lesser extent the other binary transition metal layered oxides mentioned, are known to be catalytic for heterogeneous chemical reactions such as the ORR and OER. 84 In literature, the catalytic activity of these materials can be related to the oxygen vacancies or possible formation of sub-oxides since these oxides tend to form various non-stoichiometric oxidic phases. These oxidic materials are typically synthesised on highly conductive material with large surface areas like graphene based materials.…”
Section: Structures Fabrication Routes and Basic Properties Of Commomentioning
confidence: 99%